Assessing Older Adults' Frequency of Going Outside and Physical Performance: NHATS 2017. (16th December 2020) - Sefcik, Justine; Granche, Janeway; Coates, Martha; Hathaway, Zachary; DiMaria-Ghalili, Rose Ann
Abstract: Little is known about community-dwelling older adults' outdoor activity and the relationship between physical function and frequency of going outside. Using the 2017 NHATS (N = 4, 465), we looked at self-reported outdoor frequency (Likert scale: every day to once a week or less) and the Short Physical Performance Battery (SPPB; participants completed five different physical activities to measure physical performance; total scores ranged from 0, not attempted, to 12, the best). A logistic model comparing community-dwelling older adults going out most days (18.3%), some days (10.3%), or rarely/never (3.4%) to those going out every day found ORs of 0.85, 0.70, and 0.58 respectively (all p<0.0001) for a one-unit increase in SPPB score. Interdisciplinary teams can use findings to assess disabled community-dwelling older adults' frequency of going outdoors. Implications for interventions to assist with increasing times leaving the home (e.g. mobility devices, caregiver assistance) will be discussed.